The potential use of the Penicillium chrysogenum antifungal protein PAF, the designed variant PAF(opt) and its γ‐core peptide Pγ(opt) in plant protection - Tóth, Liliána (Microb Biotechnol, 2020)
The prevention of enormous crop losses caused by pesticide‐resistant fungi is a serious challenge in agriculture. Application of alternative fungicides, such as antifungal proteins and peptides, provides a promising basis to overcome this problem; however, their direct use in fields suffers limitations, such as high cost of production, low stability, narrow antifungal spectrum and toxicity on plant or mammalian cells. Recently, we demonstrated that a Penicillium chrysogenum‐based expression system provides a feasible tool for economic production of P. chrysogenum antifungal protein (PAF) and a rational designed variant (PAF(opt)), in which the evolutionary conserved γ‐core motif was modified to increase antifungal activity. In the present study, we report for the first time that γ‐core modulation influences the antifungal spectrum and efficacy of PAF against important plant pathogenic ascomycetes, and the synthetic γ‐core peptide Pγ(opt), a derivative of PAF(opt), is antifungal active against these pathogens in vitro. Finally, we proved the protective potential of PAF against Botrytis cinerea infection in tomato plant leaves. The lack of any toxic effects on mammalian cells and plant seedlings, as well as the high tolerance to harsh environmental conditions and proteolytic degradation further strengthen our concept for applicability of these proteins and peptide in agriculture.